PELAKSANAAN EKSEKUSI HAK TANGGUNGAN SEBAGAI JAMINAN KREDIT STUDI PUTUSAN PENGADILAN NEGERI WONOSOBO - Hary Mulyadi; Nurma Khusna Khanifa; Sakti Wahyu Ningsih (SUPREMASI HUKUM, 2022)
Execution of mortgage objects is included in civil law issues. The implementation of the execution of the mortgage object has been regulated in Chapter V in Law Number 4 of 1996 concerning Mortgage Rights. This paper basically aims at academics who have an interest in civil law issues, namely the execution of mortgage objects. It is hoped that this paper will be able to provide a real picture of how the execution of mortgage objects as collateral for credit is carried out through the Class I B Wonosobo District Court and whether the implementation is in accordance with the provisions in force in Indonesia. This paper uses normative and empirical juridical research methods, namely the study of laws and regulations related to the problem, and field research to obtain information as supporting material which is then analyzed qualitatively. From the author's analysis it was found that the implementation of the execution of the mortgage object as collateral for credit through the Class I B Wonosobo District Court had been carried out properly by law enforcement and was in accordance with the provisions in force in Indonesia. Keywords: Execution of Mortgage Rights, Creditors, Debtors.